The Rise of Human Capital Theory - Blair Fix (Real-World Economics Review, 2021)
Today, human capital theory dominates the study of personal income. But this has not always been so. In this essay, I chart the rise of human capital theory, and compare it to the rise (and fall) of eugenics. The comparison, I argue, is an apt one. Eugenics and human capital theory both focus on isolated traits of individuals. By doing so, both theories neglect the social nature of human behavior.
Keywords: P16; O15; J24; 330; eugenic; human capital; income distribution; power; productivity